What Can We Expect from the "Cadillac Tax" in 2018 and Beyond? - Bradley Herring; Lisa Korin Lentz (SAGE Publishing, 2011)
One controversial aspect of the Patient Protection and Affordable Care Act is the provision to impose a 40% excise tax on insurance benefits above a certain threshold, commonly referred to as the "Cadillac tax." We use the Employer Health Benefits Survey, sponsored by the Kaiser Family Foundation and Health Research and Educational Trust, to examine the number and characteristics of plans that likely will be affected. We estimate that about 16% of plans will incur the tax upon implementation in 2018, while about 75% of plans will incur the tax a decade later due to the indexing of the tax thresholds with the Consumer Price Index. If the Cadillac tax is ultimately implemented as written, we find that it will likely reduce private health care benefits by .7% in 2018 and 3.1% in 2029, and will likely raise about $931 billion in revenue over the ensuing 10-year budget window from 2020 to 2029.